Seneca - Seneca, Lucius Annaeus, approximately 4 B.C.-65 A.D.; Basore, John W. (John William), 1870-; Gummere, Richard M. (Richard Mott), 1883-1969.; Corcoran, Thomas H.; Fitch, John G.; Seneca, Lucius Annaeus, approximately 4 B.C.-65 A.D.; Seneca, Lucius Annaeus, approximately 4 B.C.-65 A.D.; Seneca, Lucius Annaeus, approximately 4 B.C.-65 A.D.; Seneca, Lucius Annaeus, approximately 4 B.C.-65 A.D. (Cambridge, Mass. : Harvard University Press ; London : W. Heinemann, 1917)
Seneca, Lucius Annaeus, born at Corduba (Cordova) C.5 or 4 B.C. of a noble and wealthy family, spent an ailing childhood and youth at Rome in an aunt's care. He was victim of life-long neurosis but became famous in rhetoric, philosophy, money-making, and imperial service. After some disgrace during Claudius' reign he became tutor and then, in A.D. 54, advising minister to Nero, some of whose worst misdeed he did not prevent. Involved (innocently?) in a conspiracy, he killed himself by order in A.D. 65. Wealthy, he preached indifference to wealth; evader of pain and death, he preached scorn of both; and there were other contrasts between practice and principle.
v. 1-3. Moral essays -- v. 4-6. Epistulae morales -- v. 7. Naturales quaestiones I -- v. 8-9. Tragedies -- v. 10. Naturales quaestiones II.
Latin and English on opposite pages.
Vols. 1-3 translated by John W. Basore, v. 4-6 by Richard M. Gummere, v. 7 and 10 by Thomas H. Corcoran, and v. 8-9 by John G. Fitch.
Includes bibliographies and indexes.
"Bibliographical note (1987)": v. 9, p. vi.
Also issued online.
Keywords: Seneca, Lucius Annaeus, -- approximately 4 B.C.-65 A.D. -- Translations into English